Qual a importância do trabalho voluntário para sustentabilidade de organizações não-governamentais? - Nunes, Denise Cardoso Garcia (2009)
The present dissertation focuses on the voluntary work in the small private institutions without lucrative ends. The study has as its main objective to look into the voluntary work impact in the sustainability of those institutions through the non-government organization Colcha de Retalhos' study of case. The secondary objective is to analyze the motivations, meanings and benefits of the voluntary work for the volunteers. The study is characterized as descriptive-interpretative, for a predominantly qualitative approach, the data were collected through structured interviews and documental research. Important aspects for the research are revealed by the data and it fomented the study of volunteers' subjects that was brought by the interviewees, such as: citizenship and relationship tensions between, volunteers and assisted families, volunteers and schools and volunteers and volunteers and assisted families, volunteers and schools and volunteers and volunteers. Volunteers and non-governmental sector’s subjects are dealt to base the study conclusions and analysis. The results lead to a positive impact of the voluntary work in the small institutions without lucrative ends sustainability.